High-intensity interval training attenuates the effects caused by arterial hypertension in the ventral prostate - Correia, Rafael Ribeiro [UNESP]; Batista, Victor Rogério Garcia [UNESP]; Veras, Allice Santos Cruz [UNESP]; Tavares, Maria Eduarda de Almeida [UNESP]; Souza, Francilene Lima Agostinho; Pacagnelli, Francis Lopes; Campos, Dijon Henrique Salomé [UNESP]; Giometti, Ines Cristina; Teixeira, Giovana Rampazzo [UNESP] (Wiley, 2022)
Background: The prostatic effects induced by arterial hypertension is very controversial and its mechanism is unclear. High-intensity interval training (HIIT) is an exercise considered to be hypotensive. The objective of this work was to investigate the molecular, biochemical, and morphological effects of 8 weeks of HIIT in the prostatic tissue of spontaneously hypertensive rats (SHR). Methods: Twenty male SHR rats, 51.4 weeks old, were used. The SHR animals were divided into two groups: spontaneously sedentary hypertensive and spontaneously hypertensive submitted to HIIT. We analyze androgens receptor and glucocorticoid receptors in the prostate. Still, we verify effects of the hypertension and HIIT on the physiopathology prostatic, for immunohistochemistry investigated BCL-2, BAX, IGF-1, FAS/CD95, data's inflammatory tumour necrosis factor α, nuclear factor kappa B and interleukin (IL)-6, anti-inflammatory IL-10. The echocardiographic evaluation was performed at the baseline and after the training period. Results: Arterial hypertension promote high prostatic intraepithelial neoplasia incidence in the prostate, increases IGF-1, BCL-2 (p < 0.05), and inflammatory proteins (p < 0.05). Eight weeks of HIIT training reduced the arterial pressure and increase the concentration of tissue collagen and intracellular glycogen and showed a higher expression of BAX, FAS/CD95, and IL-10 proteins (p < 0.05), coinciding with a lower incidence of lesions and lower prostate weight (p < 0.05) and reduction of the BCL-2 and IGF-1. Conclusion: Our data suggested that arterial hypertension suppressed apoptosis and increased damage prostatic. On other hand, HIIT promotes morphology and function improves in the prostatic environment, inhibited inflammation, and increased apoptosis.